PENGARUH FAKTOR-FAKTOR KUALIFIKASI KONTRAKTOR TERHADAP KUALITAS PROYEK KONSTRUKSI JALAN DI KOTA BANDA ACEH - Zuhri Zuhri; Muhammad Isya; Hafnidar A.Rani (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The number of contractor companies, especially in the field of roads every year continues to increase. Based on data obtained from LPJK website (Construction Services Development Agency) Province of Aceh Year 2016, shows that from 2,717 road contractors in Aceh Province, 1% of them are big qualification, 10% middle qualification and 89% small qualification. The problem is from the increasing number of road contractor companies in Aceh Province, it has not been followed by an increase in qualification and performance. These improvements can be seen from the quality of work, the timeliness of completion of implementation, and the efficiency of resource utilization of personnel, capital, and technology. This study aims to analyze the relationship and influence between contractor's qualification factors on the quality of road construction project, and to know the dominant factor in contractor company's qualification affecting the quality of road construction project in Banda Aceh City. This study used qualitative and quantitative methods through questionnaires, where the respondents were addressed to 90 road contractor companies. The contractor company has implemented projects from 2010-2016, with funding sources from APBA. The independent variables reviewed are contractor qualification factors consisting of legal factors, technical factors, and administrative factors, while the dependent variable is the quality of road construction projects. The results show that the legal, technical and administrative factors all have a very high relationship to the quality of road construction projects in Banda Aceh City. The contractor's qualifying factors all have a significant effect on the quality of road construction projects in Kota Banda Aceh of 91.6%. The dominant factor in the qualification of contractor companies affecting the quality of road construction projects in Banda Aceh is the technical factor. This suggests that when engineering factors are improved by contractors, the quality of road construction projects will increase.